Long-Term Clinical Outcomes after Mix and Match Implantation of Two Multifocal Intraocular Lenses with Different Adds. (14th January 2019) - Jiang, Yuanfeng; Bu, Shaochong; Tian, Fang; Liang, Jingli; Wang, Tiecheng; Xing, Xiuli; Zhang, Hong; Zhang, Xiaomin
Abstract : Purpose . To compare long-term clinical outcomes between patients with bilateral implantation of +3.0 diopter (D) multifocal intraocular lenses (IOLs) and mix and match implantation of +2.5 D and +3.0 D multifocal IOLs. Material and Methods . This retrospective observer-masked cohort study comprised 66 eyes of 33 patients with two different strategies of binocular multifocal IOLs implantation: bilateral +3.0 D (17 patients) (bilateral group) and mix and match +2.5 D and +3.0 D (16 patients) (blended group). Patients were recruited 1 year (±3 months) after second-eye surgery. The primary effectiveness endpoint was binocular uncorrected intermediate visual acuity (UCIVA) at 70 cm. The secondary assessments included binocular visual quality tests and quality-of-vision questionnaire. Results . The blended group showed clinically better UCIVA (0.10 ± 0.07 logMAR) at 70 cm than the bilateral group (0.26 ± 0.09 logMAR) with a difference of 0.16 ± 0.08 logMAR (P < 0.001 ). Similar binocular visual acuities were achieved between the two groups at the near and far distance. The binocular defocus curves showed better performance in the blended group from 50 cm to 1 m. The mean binocular contrast sensitivities under the photopic conditions with or without glare and mesopic condition without glare were clinically better in the blended group. Both the groups reported low rate of visual phenomena, high rate of spectacle independence, and satisfaction. Conclusions . Comparing with bilateral implantation of +3.0 D multifocal IOLs during the cataract surgery, mix and match implantation of +2.5 D and +3.0 D multifocal IOLs provides a wider depth of binocular focus, especially for intermediate distances, and better binocular visual quality.